2017
DOI: 10.1002/ijgo.12103
|View full text |Cite
|
Sign up to set email alerts
|

A preoperative and intraoperative scoring system to predict nodal metastasis in endometrial cancer

Abstract: A highly accurate scoring system for the prediction of lymph node metastasis was developed on the basis of three preoperative and intraoperative risk factors. After validation, this model could greatly aid clinicians in the surgical management of endometrial cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…So far, routine procedures for EC staging and treatment are total hysterectomy and bilateral salpingo-oophorectomy, including pelvic and para-aortic lymphadenectomy [4]. However, whether lymph node dissection (LND) could be applied for endometrial cancer patients remains a controversial issue, either in stage I or in a higher stage [5, 6]. Many debates about the role of lymphadenectomy exist.…”
Section: Introductionmentioning
confidence: 99%
“…So far, routine procedures for EC staging and treatment are total hysterectomy and bilateral salpingo-oophorectomy, including pelvic and para-aortic lymphadenectomy [4]. However, whether lymph node dissection (LND) could be applied for endometrial cancer patients remains a controversial issue, either in stage I or in a higher stage [5, 6]. Many debates about the role of lymphadenectomy exist.…”
Section: Introductionmentioning
confidence: 99%
“…There are three distinct risk groups for lymph node metastasis, defined with some variations depending on the published study: (1) low risk (27% of the cases, with disease in an initial stage and up to 50% MI and G1), with lymph node metastasis found in <5%. In these cases, the staging surgery may be restricted to total hysterectomy and bilateral salpingo-oophorectomy (BSO) [6,[11], [12], [13]]; (2) the opposite group, at high-risk (24% of the cases, with >50% MI and G3), with lymph node metastasis found in 25%–40%. This group has indication for systematic lymphadenectomy (SL) of the pelvic and para-aortic region, for the correct staging of the neoplasm [[13], [14], [15]]; (3) the third group, at intermediate risk (at least 50% of all cases, when considered endometrioid endometrial carcinoma (EEC) with up to 50% MI and G2 or G3 (FIGO Stage IAG2 or IAG3), and tumors with deep MI (>50%) and G1 or G2 (FIGO Stage IBG1 or IBG2) [13,16], with lymph node metastasis rate between 5% and 25%.…”
Section: Introductionmentioning
confidence: 99%
“…Other models did not include critical data, or were lacking demographic information, biochemical indicators or immunohistochemical markers for cancer lesions. 17,28,34 Some other models described scoring indicators that are not commonly used in the clinic, for example, a tumor volume ≥6 cm 3 was considered as a high-risk factor for LNM 33 ; in other studies, the cut-off value for CA125 was set to 27.6 U/mL or 30 U/mL. 18,26 In some models, unstable parameters were used, including complete blood count (e.g., high risk was previously defined by: thrombocytes >360 × 10 9 /L, leukocytes >8.2 × 10 9 /L); such parameters are susceptible to fluctuations.…”
Section: Discussionmentioning
confidence: 99%
“…reported that some models were associated with poor prediction accuracy and low specificity (5.4 – 37.6%); consequently, these models were not able to accurately identify patients with negative LNM. Other models did not include critical data, or were lacking demographic information, biochemical indicators or immunohistochemical markers for cancer lesions 17,28,34 . Some other models described scoring indicators that are not commonly used in the clinic, for example, a tumor volume ≥6 cm 3 was considered as a high‐risk factor for LNM 33 ; in other studies, the cut‐off value for CA125 was set to 27.6 U/mL or 30 U/mL 18,26 .…”
Section: Discussionmentioning
confidence: 99%